Novel Series Resonant High-Voltage Dc-Dc Converter Topologies For X-Ray Systems - Lee, Sze Sing (2013)
Conventional pulse-frequency-modulated (PFM) series resonant high-voltage (HV) direct-current (DC) power supplies have the limitations of poor controllability at light load, high conduction loss, large output voltage ripple, slow transient response and high current stress on circuit components at low switching frequencies. This thesis proposes four novel topologies of HV DC-DC converters, namely, ZCSSR (zero current switching - series resonant) inverter-fed, ZCS-SR inverter-fed voltage multiplier (VM) based, ZCS-DSR (zero current switching - double series resonant) inverter-fed and ZCS-DSR inverter-fed VM based. First and second topologies are controlled by using digital tuning of tank capacitance and variable pulse frequency with dual-mode operation. Third and fourth topologies are controlled by PFM with dual-mode operation. The effectiveness of all the proposed power converter topologies and corresponding control scheme are verified by simulation and experimental results. First and second converters have superior performances compared to the conventional PFM converter in terms of their wider range of output voltage controllability, lower percent ripple, lower current stress on circuit components and higher efficiency. The main features of third and fourth proposed converters are that they are highly efficient and have very simple circuit operations. Among all the proposed converters, the ZCS-SR inverter-fed VM based HV DC-DC converter is the best choice for X-ray systems with the power range from 100W to 350W. The measured efficiency at 100W is 87% and 92% at 350W.